Is Increased Video Game Participation Associated With Reduced Sense of Loneliness? A Systematic Review and Meta-Analysis - Luo, Yan; Moosbrugger, Michelle; Smith, Daniel M.; France, Thaddeus J.; Ma, Jieru; Xiao, Jinxiang (Frontiers in Public Health, 2022)
The purpose of this systematic review was to evaluate the existing evidence in literature addressing the relationship between video game participation and loneliness. The following databases were searched on October 2, 2021: Medline, Psychinfo, SportDiscus, Web of Science, and CINAHL. The risk of bias of cross-sectional study was assessed by using the Joanna Briggs Institute (JBI) critical appraisal checklist for analytical cross-sectional studies with attrition bias added for longitudinal studies. The results of all included studies were synthesized using narrative synthesis. Meta-analysis was utilized to synthesis the findings of the studies that had sufficient degree of statistical and methodological homogeneity. 18 studies were included in this systematic review, which comprised of 20372 participants. The narrative synthesis showed mixed findings on the relationship between video game participation and loneliness. Meta-analysis that was conducted to nine cross-sectional studies revealed that video game participation was positively and weakly associated with loneliness (r = 0.10, 95%CI = 0.03-0.17). Both cross-sectional and longitudinal studies demonstrated serious risk of bias with the addition of serious inconsistency of findings from cross-sectional studies. The existing literature is equivocal in terms of making a definitive judgment on the association between video game participation and loneliness. PROSPERO registration number: CRD42021283025.